Answering contemporary doubts about the Qur'an: In the context of its preservation, compilation, and authenticity - Said Nawab; Dr.Qazi Abdul Manan; Attaullah (Journal of Religion and Society, 2025)
Muslims have always considered the Quran as the word of Allah that was revealed to Prophet Mohammad and is preserved with perfect accuracy. However, today, different critics, especially those who are influenced by the Orientalist studies and secular ideology, have questioned its collection, authenticity and continuity through history. These arguments of objection usually assert that the compilation of the Quran was a mere human action, that different versions of the text contradict the unity of text, that the initial codices of the Companions are non-identical with the official Uthmanic edition. Other criticisms indicate political reasons in its compiling, or claim historical and scientific error. This paper presents such modern myths in an organized manner based on historical, textual, and logical pieces of evidence. It shows that the preservation process started in the lifetime of the Prophet Muhammad, ﷺ, when the Quran was memorized by several of his companions and it was written down by special scribes. After the death of the Prophet, Abu Bakr (RA) ordered the first manuscript that had been gathered to be done with the control of Zayd ibn Thabit (RA), one of the immediate scribes of revelation. The Caliph Uthman (RA), later with the agreement of the senior Companions came up with a standard Quranic text as a way of maintaining unity and avoiding disagreement in the recitation. This attempt was not politically inclined but a communal religious duty of the Muslim society. The nature of Qur’anic variant readings (qirā’at) is also explained in the paper with clear understanding that Quranic variant readings are not textual corruptions but are genuine linguistic variations that have been propagated by mass consensus (tawataur) to amplify meaning without distorting the doctrine. The claims of textual divergence among the privately produced codices of Companions are attributed to their use as teaching notes, but not as official text. On the same note, assertions of lost verses or abrogated passages are also discussed in the context of the Islamic sciences, as being a difference between abrogation of recitation and unsubstantiated ideas about the loss of the text. Moreover, the paper underlines that the Quran is not a science text but a guidance book and the perceived conflict with scientific theory is therefore either a result of an erroneous interpretation of the text, or the tentative character of science. The fact that the Quran has been transmitted universally, the millions of memorizers throughout the centuries, and the same copies have been preserved in various parts of the world is a living testimony of the authenticity of the Quran. Finally, the article restates the fact that the Quran has stayed the same by the promise of God, the continuation of history and the unanimous agreement of Muslim Ummah. There is a need to address the doubts in a scholarly manner. Keywords: Qur’an Preservation, Compilation of the Qur’an, Variant Readings (Qirā’āt), Orientalist Criticism, Authenticity of the Qur’an, Uthmanic Codex, Contemporary Doubts